2019
DOI: 10.1007/s13205-019-1595-x
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific loop-mediated isothermal amplification (LAMP) assay for identification of tissue of cattle origin by targeting mitochondrial gene sequences

Abstract: The present study was carried out with the objective of development of species-specific loop-mediated isothermal amplification (LAMP) assay for identification of tissue of cattle origin. The cattle-specific LAMP primer set was designed by targeting mitochondrial D-loop gene. The conditions for LAMP reaction for amplification of template DNA from cattle using designed cattle-specific primer set were optimized for the components of mixture and temperature of reaction. Amplified products were analysed using SYBR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The results had shown that all samples could be detected by two T lines and found that the 5% duck in beef can be easily detected ( Figure 4 ). We were not pursuing a lower proportion because it was difficult to obtain any commercial profit from the 5% adulteration of low-quality meat in actual manufacturing and sales, which was in good agreement with the data reported in many previous reports [ 35 , 36 ]. In addition, the sensitivity test was also conducted for each species, a dilution series of beef and duck DNA with concentrations ranging from 100 to 0.01 ng were performed.…”
Section: Resultssupporting
confidence: 90%
“…The results had shown that all samples could be detected by two T lines and found that the 5% duck in beef can be easily detected ( Figure 4 ). We were not pursuing a lower proportion because it was difficult to obtain any commercial profit from the 5% adulteration of low-quality meat in actual manufacturing and sales, which was in good agreement with the data reported in many previous reports [ 35 , 36 ]. In addition, the sensitivity test was also conducted for each species, a dilution series of beef and duck DNA with concentrations ranging from 100 to 0.01 ng were performed.…”
Section: Resultssupporting
confidence: 90%
“…Such assessments usually involve the analysis of mitochondrial genes, i.e., cytochrome b (cytb) and cytochrome c oxidase subunits I and II (cox1 and cox2), and the control region (CR) [62]. Food frauds are especially prevalent in poor and developing countries with high populations, where the demand for meat and meat products is rising, which inflates their prices [63]. Subject literature contains an increasing number of reports on pork frauds and their detectability with LAMP [64][65][66][67][68].…”
Section: Application Of Lamp In Forensicsmentioning
confidence: 99%
“…The most common targets of fraud are pork and beef products [63]; however, not enough tests have been designed to date. Some of the available tests can detect pork at a concentration of 0.01% in the mixture, which corresponds to 0.1 g of pork in 1 kg of meat [64,69,70].…”
Section: Application Of Lamp In Forensicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test accuracy is the primary concern. At present, the accuracy of PCR testing technology has reached near 100% ( Dharavath et al, 2020 ; Garg et al, 2020 ), while its capability to detect a positive individual in a pooled sample is between 100 and 1000 individuals ( Dharavath et al, 2020 ; Kumari et al, 2019 ). Thus, within a mixture of 1000 samples, the applied PCR method is sensitive enough to identify the presence of the virus from a single sample.…”
Section: Methodsmentioning
confidence: 99%